THE GEOCHEMISTRY AND PROVENANCE OF APOLLO 16 MAFIC GLASSES - Zeigler R.A.; Korotev R.L.; Jolliff B.L.; Haskin L.A.; Floss C. (My University, 2006)
The regolith of the Apollo 16 lunar landing site is composed mainly of feldspathic lithologies but mafic lithologies are also present. A large proportion of the mafic material occurs as glass. We determined the major element composition of 280 mafic glasses (>10 wt% FeO) from six different Apollo 16 soil samples. A small proportion (?5%) of the glasses are of volcanic origin with picritic compositions. Most, however, are of impact origin. Approximately half of the mafic impact glasses are of basaltic composition and half are of noritic composition with high concentrations of incompatible elements. A small fraction have compositions consistent with impact mixtures of mare material and material of the feldspathic highlands. On the basis of major-element chemistry, we identified six mafic glass groups: VLT picritic glass, low-Ti basaltic glass, high-Ti basaltic glass, high-Al basaltic glass, KREEPy glass, and basaltic-andesite glass. These glass groups encompass ?60% of the total mafic glasses studied. Trace-element analyses by secondary ion mass spectroscopy for representative examples of each glass group (31 total analyses) support the major-element classifications and groupings. The lack of basaltic glass in Apollo 16 ancient regolith breccias, which provide snapshots of the Apollo 16 soil just after the infall of Imbrium ejecta, leads us to infer that most (if not all) of the basaltic glass was emplaced as ejecta from small- or moderate-sized impacts into the maria surrounding the Apollo 16 site after the Imbrium impact. The high-Ti basaltic glasses likely represent a new type of basalt from Mare Tranquillitatis, whereas the low-Ti and high-Al basaltic glasses possibly represent the composition of the basalts in Mare Nectaris. Both the low-Ti and high-Al basaltic glasses are enriched in light-REEs, which hints at the presence of a KREEP-bearing source region beneath Mare Nectaris. The basaltic andesite glasses have compositions that are siliceous, ferroan, alkali-rich, and moderately titaniferous; they are unlike any previously recognized lunar lithology or glass group. Their likely provenance is within the Procellarum KREEP Terrane, but they are not found within the Apollo 16 ancient regolith breccias and therefore were likely deposited at the Apollo 16 site post-Imbrium. The basaltic-andesite glasses are the most ferroan variety of KREEP yet discovered.
Keywords: CHEMICAL COMPOSITION; GEOCHEMISTRY; LUNAR SOIL; PROVENANCE; REGOLITH; TRACE ELEMENT